New Gene Combinations Conferring Resistance to the Bacterial Blight Disease of Cotton - M. Abdalla, Khalid; M. Mustafa, Ahmed; S. Ibrahim, Abu Elhassan (Gezira Journal of Agricultural Science; Vol 2 No 1 (2004), 2021)
F 2 plants comprising different gene combinations were evaluated for cotton bacterial blight resistance in the field of the Gezira Research Station and the greenhouse of the Plant Pathology Centre of the University of Gezira, Neshashiba, Wad Medani, during the autumn of 2002. Results generally showed significant differences between different gene combinations in resistance to the new race of the bacterium Xanthomonas campestris pv. malvacearum . Leaf disease grades ranged from 4 to 6. Most of the plants fell into grade 5. Genotype 12, with expected gene combination of (B 2 B 3 B 6 B 7 B 9 B 12 ), expressed the highest level of resistance with a mean disease grade of 4, while genotypes 7, 11 and 15 showed the lowest level of resistance with a mean disease grade of 6. The results indicated the importance of the genetic background B 2 B 3 B 7 in improving resistance to both the old and the new races when one of the following major genes B 4 , B 6 , B 9 , and B 12 is incorporated. In such background, resistance level improves as the number of genes increases. Therefore, the commercial resistant cultivars having B 2 B 6 genetic background to the old race of the bacterium can be replaced by the genetic background involving B 2 B 3 B 7 in addition to one of the four major genes mentioned above in order to protect the cotton crop. Genotypes 5, 6, 12, and 19 were recommended for further improvement as they expressed relatively high level of resistance to the pathogen.